In vitro antiviral activity of Fisetin, Rutin and Naringenin against Dengue virus type-2 - Zandi, K.; Teoh, B.T.; Sam, S.S.; Wong, P.F.; Mustafa, Mohd Rais; AbuBakar, Sazaly (2011)
In vitro antiviral activities of three flavonoids; fisetin, naringenin and rutin against DENV-2 (NGC strain) were evaluated. Inhibitory effects of each compound at the different stages of DENV-2 infection were examined using foci forming unit reduction assay (FFURA) and quantitative real-time polymerase chain amplification (qRT-PCR). Fisetin, rutin and naringenin showed cytotoxic effects against Vero cells with 50 cytotoxicity (CC(50)) values of 247, > 1000, and 87 mu g/mL, respectively. Fisetin when added to Vero cells after virus adsorption inhibited DENV replication with a half maximal inhibition concentration (IC(50)) value of 55 mu g/mL and selectivity index (SI) of 4.49. The IC(50) value of fisetin was 43.12 mu g/mL with SI=5.72 when Vero cells were treated for 5 h before virus infection and continuously up to 4 days post-infection. There was no direct virucidal activity or prophylactic activity of fisetin against DENV-2. Rutin and naringenin did not inhibit DENV-2 replication in Vero cells. Naringenin however, exhibited direct virucidal activity against DENV-2 with IC(50) = 52.64 mu g/mL but the SI was <1. The present study suggests that among the flavonoids examined, only fisetin showed significant in vitro anti dengue virus replication activity.